2020
DOI: 10.1021/acschembio.0c00220
|View full text |Cite
|
Sign up to set email alerts
|

The Progesterone 5β-Reductase/Iridoid Synthase Family: A Catalytic Reservoir for Specialized Metabolism across Land Plants

Abstract: Iridoids are plant-derived terpenoids with a rich array of bioactivities. The key step in iridoid skeleton formation is the reduction of 8-oxogeranial by certain members of the progesterone 5β-reductase/iridoid synthase (PRISE) family of short-chain alcohol dehydrogenases. Other members of the PRISE family have previously been implicated in the biosynthesis of the triterpenoid class of cardenolides, which requires the reduction of progesterone. Here, we explore the occurrence and activity of PRISE across major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…MVK was accepted much better by r Dl P5βR1 than by r Dl P5βR2 indicating that Dl P5βR1 and Dl P5βR2 may play different roles within the plant. Differences in substrate specificity were similarly observed in other orthologue PRISEs in different plant species, such as Medicago, Catharanthus, Erysimum , and Arabidopsis (Munkert et al 2015a , b ; Nguyen and O’Connor 2020 ).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…MVK was accepted much better by r Dl P5βR1 than by r Dl P5βR2 indicating that Dl P5βR1 and Dl P5βR2 may play different roles within the plant. Differences in substrate specificity were similarly observed in other orthologue PRISEs in different plant species, such as Medicago, Catharanthus, Erysimum , and Arabidopsis (Munkert et al 2015a , b ; Nguyen and O’Connor 2020 ).…”
Section: Resultsmentioning
confidence: 67%
“…Moreover, P5βR-like enzymes (termed iridoid synthases; ISY) are involved in iridoid biosynthesis (Geu-Flores et al 2012 ), and Munkert et al ( 2015a , b ) reported that iridoid synthase activity is common among the plant progesterone 5β-reductase family. More recently, the enzymes progesterone 5β-reductase/iridoid synthase-like enzymes were termed PRISEs (Schmidt et al 2018 ) and described as a catalytic reservoir for specialized metabolism across land plants (Nguyen and O’Connor 2020 ). Progesterone in cardenolide biosynthesis and 8-oxogeranial in iridoid synthesis are not the only substrates for PRISEs.…”
Section: Introductionmentioning
confidence: 99%
“…The broad substrate spectrum of many P450s can complicate biosynthesis studies and metabolic engineering efforts ( Hidalgo et al, 2017 ; De La Peña and Sattely, 2021 ). Nevertheless, such promiscuity sheds light into the evolution of these enzymes, and indicates their crucial role as part of the catalytic reservoirs whose members can be recruited for emerging pathways and further drive the chemical diversity of plants ( Tawfik, 2010 ; Ikezawa et al, 2011 ; Weng et al, 2012 ; Guo et al, 2016 ; Dang et al, 2017 , 2018 ; Forman et al, 2018 ; Christ et al, 2019 ; Nguyen et al, 2019 ; Lichman et al, 2020 ; Nguyen and O’Connor, 2020 ). Even for non-native or new-to-nature substrates including halogenated analogues, P450s display a certain degree of natural tolerance as observed in the multiple-step biotransformation of 7-chlorotryptamine to 12-chloro-19,20-dihydroakuammicine in MIA metabolism of C. roseus cultures ( Glenn et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme iridoid synthase (ISY) then performs a 1,4 reduction of 8-oxogeranial to yield a reactive intermediate (8-oxocitronellyl enol) that can then spontaneously cyclize to form predominantly the cis,trans stereoisomer of nepetalactol (Geu-flores et al 2012 ; Miettinen et al 2014 ; Kries et al 2017 ; Nguyen and O’Connor 2020 ). Although ISY is found ubiquitously in all iridoid producing plants (Nguyen and O’Connor 2020 ), a detailed phylogenetic analysis (Mint Evolutionary Genomics Consortium 2018 ) suggests that ISY was lost in the Nepetoideae sub-family, and then re-evolved independently in the Nepeta genus from progesterone-5-beta reductase (P5βR). Thus, Nepeta ISY has a distinct catalytic active site compared to the ISY found in other iridoid producing plants (Sherden et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%